Dienstmädchen – von romantisierten Zuschreibungen und menschenunwürdigen Arbeits- und Lebensbedingungen, damals wie heute. - Göddertz, Nina (Soziale Frauenberufe in Ost und West)

Insights into the current situation of technological education at primary schools – illustrated by the example of Germany - Schneider, Lea; Tenberge, Claudia (The 42nd Pupils' Attitudes Towards Technology Conference)

Visitor Revival Propositions for Cultural Institutions – A Service Science Perspective - Hansmeier, Philipp; Althaus, Maike (Journal of Service Management Research)

ARTIFICIAL INTELLIGENCE IN DIGITAL SERVICE ECOSYSTEMS – A TAXONOMY APPROACH - Hansmeier, Philipp; Schäfer, Jannika Marie (Thirty-Third European Conference on Information Systems)

CONCEPTUALIZING A CUSTOMER EXPERIENCE FRAMEWORK FOR HYBRID (PHYSICAL-DIGITAL) SERVICE ECOSYSTEMS - Hansmeier, Philipp (Thirty-Third European Conference on Information Systems)

Service Innovation through Data Ecosystems – Designing a Recombinant Method - Hansmeier, Philipp; zur Heiden, Philipp; Beverungen, Daniel (Proceedings of the 20th International Conference on Wirtschaftsinformatik (WI25))

Ecosystem-Level Customer Experience with Smart Service: Insights from a Systematic Scoping Literature Review - Hansmeier, Philipp; Beverungen, Daniel (Journal of Service Management Research)
Smart service is fundamentally transforming customer experience in both commercial and private contexts. While the information systems and service disciplines have explored the properties and implementation of smart service, there is a gap in understanding how smart service relates to customer experience at the ecosystem level. With the increasing prominence of digital platforms and data spaces, this ecosystem perspective will become crucial for the success of smart service. We report findings from a systematic scoping literature review on smart service themes and related customer experience concepts. Our analysis of 26 high-quality papers reveals three key insights: (1) smart service systems play a pivotal role in enabling customer experience, (2) customer experience in smart service scenarios is often co-created through “hybrid” customer journeys, and (3) these scenarios are subject to an ecosystem-level. Additionally, we identify smart service fundamentals, embeddedness levels, and business innovation as core themes that shape ecosystem-level customer experience.

Molecular Orientation‐Dependent Photonic Spin–Orbit Coupling in Organic Microcavities Filled with 2D Polymorphic Crystals - Ji, Ying; Ma, Xuekai; Huang, Han; Deng, Yibo; Wang, Pingyang; Long, Teng; Li, Yuan; Zhao, Ruiyang; Li, Yunfei; An, Cunbin; Schumacher, Stefan; Gu, Chunling; et al. (Laser & Photonics Reviews)
ABSTRACT Effective manipulation of photonic spin–orbit coupling (SOC) in microcavities is of fundamental importance within topological photonics and applications. Anisotropic organic single‐crystalline materials can induce abundant SOC phenomenon due to their flexible tunability of molecular geometries, however, the intrinsic relationship between molecular geometries/orientations in 3D space and photonic SOC is lacking. In this study, we design two kinds of 2D organic polymorphs for the construction of organic microcavities to investigate the structure‐performance relationships. In two polymorphic microcavities, two distinctive photonic SOC phenomena are observed regardless of the in‐plane anisotropy of organic polymorphs. Theoretical analysis indicates that the photonic SOC strength is strongly influenced by the synergies between the crystal anisotropy and the tilted collective molecular transition dipole moment. Our results uncover the correlation mechanism between the structure of molecules and photonic SOC and open an avenue to engineer complex photonic SOC by use of organic microstructures towards the development of diverse integrated photonic devices.

Tuning polariton vortices in an asymmetric ring potential - Ai, Qiang; Ma, Xuekai; Barkhausen, Franziska; Zhai, Xiaokun; Xing, Chunzi; Yang, Xinmiao; Wang, Peilin; Liu, Tianyu; Zhang, Yong; Gu, Yazhou; Li, Peigang; Li, Zhitong; et al. (Applied Physics Letters)
Exciton polariton condensates are macroscopic coherent states in which topological excitations can be observed. In this work, we observe the excitation of the vortices and realize tuning the topological charge by manipulating the pumping configurations. Using a digital micromirror device, we constructed an annular pumping pattern where the inner and outer rings can be easily tuned. Both the number and the topological charge of the vortices can be changed by slightly tuning the inner ring position against the outer ring. The experimental results can be reproduced in theory by the Gross–Pitaevskii equation. Our work offers to generate and manipulate vortices in exciton polariton condensates using a straightforward optical method.

Higher-order dark solitons and control dynamics in microcavity polariton condensates - Sun, Jinming; Chen, Manna; Schumacher, Stefan; Hu, Wei; Ma, Xuekai (Physical Review B)

In Situ PM‐IRRAS and XPS Analysis of Nitrogen Plasma Surface Modification of Polylactide Thin Films - Gołębiowska, Sandra; Voigt, Markus; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Surface and Interface Analysis)
ABSTRACT Spin‐coated polylactide (PLA) thin films were exposed to nitrogen plasma for varying time intervals. The progressive etching of the PLA film in direct contact with the nitrogen plasma was monitored in situ using polarization modulated infrared reflection absorption spectroscopy (PM‐IRRAS). No appreciative changes in composition were seen with PM‐IRRAS, indicating that the etching did not significantly affect the bulk composition. Atomic force microscopy characterization of the plasma‐etched films showed that the PLA films are homogeneously etched. Subsequent ex situ XPS analysis of the treated surface revealed the presence of C‐N bonds in the surface‐near region that could be associated with amino and/or amide surface species. PLA films were also alternatively exposed to nitrogen ion beams produced by an electron‐cyclotron‐resonance (ECR) plasma source and were investigated in vacuo by XPS. This treatment revealed the partial substitution of surface oxygen species by nitrogen, resulting in a similar surface modification as in the plasma case. The comparison of XPS data and water contact angle studies suggest that the activated surfaces show a reorientation of macromolecular fragments in the surface‐near region depending on the polarity of the phase with which they are in contact. Under ultra‐high vacuum (UHV) conditions, the surface tends to lower its surface energy, while in contact with the aqueous phase, subsurface polar groups orientate outwards, which enables the formation of hydrogen bonds.

Learning to teach and teaching to learn about Robotics Professionalization for inclusive technology education integrating theory and practice - Osnabrügge, Malin; Schemel, Nele; Schneider, Lea; Schröer, Franz; Tenberge, Claudia (Zukünfte technischer Bildung)

Selbstwirksamkeitserwartungen zur methodischen Gestaltung eines gemeinschaftsorientierten und partizipativ-verfahrensorientierten Unterrichts: Entwicklung von Kurzskalen zur schulischen Demokratiebildung - Wehde, Janis (Zeitschrift für Bildungsforschung)

Evaluation of anti-adhesive and corrosion protection properties of TiAlSiN-magnetron-sputtered films for applications in polymer processing - Theile-Rasche, Chantal; Wang, Fuzeng; Prüßner, Tim; Huck, Marten; Steinrück, Hans-Georg; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Thin Solid Films)

DNA origami adsorption at single-crystalline TiO2 surfaces - Xu, Xiaodan; Gołębiowska, Sandra; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido; Keller, Adrian (RSC Applied Interfaces)
DNA origami adsorption at single-crystalline TiO 2 surfaces is investigated at different Mg 2+ concentrations. For TiO 2 (001), DNA origami adsorption is stronger at 5 mM than at 10 mM Mg 2+ , whereas the opposite is observed for TiO 2 (110) and TiO 2 (111).

High-fidelity quantum entanglement distribution in metropolitan fiber networks with co-propagating classical traffic - Sena, Matheus; Flament, Mael; Andrewski, Shane; Caltzidis, Ioannis; Bigagli, Niccolò; Rieser, Thomas; Bello Portmann, Gabriel; Sekelsky, Rourke; Braun, Ralf-Peter; Craddock, Alexander N.; Schulz, Maximilian; Jöns, Klaus; et al. (Journal of Optical Communications and Networking)
The Quantum Internet, a network of quantum-enabled infrastructure, represents the next frontier in telecommunications, promising capabilities that cannot be attained by classical counterparts. A crucial step in realizing such large-scale quantum networks is the integration of entanglement distribution within existing telecommunication infrastructure. Here, we demonstrate a real-world scalable quantum networking testbed deployed within Deutsche Telekom’s metropolitan fibers in Berlin. Using commercially available quantum devices and standard add-drop multiplexing hardware, we distributed polarization-entangled photon pairs over dynamically selectable looped fiber paths ranging from 10 m to 60 km and showed entanglement distribution over up to approximately 100 km. Quantum signals, transmitted at 1324 nm (O-band), coexist with conventional bidirectional C-band traffic without dedicated fibers or infrastructure changes. Active stabilization of the polarization enables robust long-term performance, achieving entanglement Bell-state fidelity bounds between 85% and 99% and Clauser–Horne–Shimony–Holt parameter S -values between 2.36 and 2.74 during continuous multiday operation. By achieving a high-fidelity entanglement distribution with less than 1.5% downtime, we confirm the feasibility of hybrid quantum-classical networks under real-world conditions at the metropolitan scale. These results establish deployment benchmarks and provide a practical roadmap for telecom operators to integrate quantum capabilities.

Digital-gestützt lehren lernen. Technisches Problemlöser am Übergang von G zu Sek I - Osnabrügge, Malin; Tenberge, Claudia (Posterbeitrag im Rahmen der Jahrestagung der Deutschen Gesellschaft für Technischen Bildung (DGTB) vom 18-19.09.2025 in Chemnitz)

Anschluss begleiten: Technisches Lernen zwischen Primar- und Sekundarstufe. Fortbildungen für einen digitalen Unterricht für alle - Osnabrügge, Malin; Tenberge, Claudia (Posterbeitrag im Rahmen der Jahrestagung der DGFE Sekten Sonderpädagogik vom 22-24.09.2025 in Heidelberg)

(Peer-)Feedback mit Respekt! Gutes und respektvolles Feedback verfassen. - Rezat, Sara (Praxis Deutsch)

Teachers’ professional attitudes toward Muslim religious norms: studying the organizational context of moral position-taking - Koch, Annika (ZISU – Zeitschrift für interpretative Schul- und Unterrichtsforschung)
Many studies to date have shown how teachers disadvantage Muslim students due to unconscious bias. Much less is known about how teachers’ attitudes are influenced by the organizational context of their schools. I aim to contribute to filling this research gap by analyzing interviews with teachers at high schools with a large share of Muslim students. I show how my interview partners were forced to position themselves according to the religious norms of their students and the secularized Christian norms that are often taken for granted in the German school system. My interview partners adopted various ethical perspectives. However, their positioning was always ambivalent and linked to both recognizing their students’ backgrounds and distancing themselves from this.